A day in the life with an automated vehicle: Empirical analysis of data from an interactive stated activity-travel survey. (June 2021) - Pudāne, Baiba; van Cranenburgh, Sander; Chorus, Caspar G.
Abstract: Fully Automated Vehicles (AVs) have been widely expected to revolutionise the future travel experience. Recent studies have shown that their impact may also reach beyond the travel episode, and lead their users to alter other activities performed during the day – their daily lifestyles. This study is among the first to empirically investigate the changes that travellers expect in their daily activities with AVs. To this aim, we created an interactive stated activity-travel survey, in which respondents designed their current daily schedule and, following that, redesigned it while imagining that their most frequently used travel mode is replaced with an AV. We administered the survey to 509 commuters in the Netherlands and analysed (changes in) on-board and stationary activity patterns using the multiple discrete-continuous extreme value (MDCEV) model. Results show a clear increase in the prevalence of various on-board activities in the AV compared to current modes, and even stronger increase for the high income and higher educated groups. Changes in stationary activities are less pronounced: no changes in the aggregate, but some changes within particular socio-demographic groups. Specific changes in stationary activities were associated with specific changes in on-board activities for the higher educated respondents: switching to AVs, they were more likely than others to add on-board work, meals, and leisure to their trips and more likely to add a getting ready activity to their stationary schedules. This study contributes to the growing body of literature that recognises and models on-board activities as an integral part of daily schedules. Highlights: With an interactive activity-travel survey we collected pre- and post-AV schedules. Using MDCEV we modelled (changes in) on-board and stationary activity patterns. On-board activities increase with AVs, and more so with high income and education. Stationary activities do not change in aggregate, only in some demographic groups. For the higher educated, changes in stationary and on-board schedules may be related.